ANTECEDENTS OF THE INTERROLE CONFLICT AND ITS RELATIONSHIP WITH GENDER SELF-SCHEMA - Martínez Vera, Carmen; Vera, Juan José; Paterna Bleda, Consuelo; Rosa Alcázar, Ana Isabel (Anales de Psicología / Annals of Psychology, 2002)
The relationship between work and family has been explained from spillover theory (Piotrkowski, 1978) although conflict theory (Greenhaus y Beutell, 1985) also has been confirmed. However, the literature has not considered the gender approach. This study analyses the relationship work-family trough different roles, its satisfaction and its relationship with interrole conflict. Besides, we propose a relationship between self-schema gender and antecedents of interrole conflict. 107 mothers employees participated in the study. Results suggested that family roles are more important for women, and produce more satisfaction, than work roles. Also appear different predictors of conflict depending on self-schema gender. The results are commenting in relation to spillover theory and work and family characteristics of participants.